Pengaruh Fraksi Volume Dan Sudut Konfigurasi Serat Phyllostachys Terhadap Kekuatan Komposit Dengan Metode Hand Lay-Up - ., Weriono; Junaidi, Abdulkhair; ., Rinaldi; Isra, Adi; Kurniawan, Mauliade (Rekayasa Material, Manufaktur dan Energi, 2022)
Plyllostachys bamboosoides known in Asia, also called bamboo fence, is one of the choices for the construction and manufacture of furniture. Its properties also make it useful in a number of arts and crafts. The influence of ductility and toughness factors is at the microcellular level; which includes the pattern of arrangement, morphology, and mechanical properties of bamboo cells. The perfect combination of fibers and compressible parenchyma cells is the key to the excellent flexible deformation of bamboo, originally illustrated the elongation of parenchyma cells under bending through low resolution electron micrographs. The angle of the microfibrils in the cell wall plays an important role in the mechanical properties of the wood and the occurrence of interface delamination followed by matrix failure and fiber breakdown under natural growth. Tensile strength and strain due to the influence of variations in thickness and volume of composite composition with variations in manufacturing methods that can affect its mechanical properties so that it is expected to determine a good composition. The addition of bamboo fiber as a filler of Polyester resin has a significant effect on the tensile strength. Tensile testing with an angle of 450 with a thickness 1 mm resulted in the highest ultimate stress 0.027 M.Pa with 25%:75% polyester resin of bamboo fiber. The tensile strength is increased by increasing the volume of the bamboo fiber and reducing the thickness of the bamboo fiber increases the tensile strength of the composite.